2022
DOI: 10.4102/jamba.v14i1.1202
|View full text |Cite
|
Sign up to set email alerts
|

Effects of climate change on pastoral households in the Harshin District of the Somali Region, Ethiopia

Abstract: This study was conducted in the Harshin District of the Somali Region, Ethiopia, to understand the climate change trends, their consistency with pastoralists’ perceptions and their effects on pastoral households. The study used both qualitative and quantitative data collected from 143 households through household surveys. Focus group discussions and key informant interviews were also employed to triangulate and substantiate the reports from household surveys. Data were analysed using Statistical Package for So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In Kaabong district, Karamoja region in Uganda, salvage sale losses contributed 7.2% of economic cost due cattle diseases per household [35]. Elsewhere these effects were also most felt among the pastoral communities in Kenya [36, 37,38], in Ethiopia [39,40,41], in Burkina Faso [42] and in Nigeria [34]. Earlier work done in the study area [14] showed that the economic cost of drought among cattle in this area was less severe.…”
Section: Discussionmentioning
confidence: 99%
“…In Kaabong district, Karamoja region in Uganda, salvage sale losses contributed 7.2% of economic cost due cattle diseases per household [35]. Elsewhere these effects were also most felt among the pastoral communities in Kenya [36, 37,38], in Ethiopia [39,40,41], in Burkina Faso [42] and in Nigeria [34]. Earlier work done in the study area [14] showed that the economic cost of drought among cattle in this area was less severe.…”
Section: Discussionmentioning
confidence: 99%
“…The possible explanation for this could be residents in the Somali region relatively have low access to health infrastructure, education, and informational resources in comparison to Tigray [ 32 ]. The finding could also be explained by the fact that the Somali region experiences extremely high temperatures throughout the year, both during the day and less cooling overnight [ 33 ]. This has an impact on the health of humans, especially that of small children, and may contribute to an increase in infant mortality in the area.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in Ethiopia have indicated that rural communities often possess limited knowledge about AMR [15,16]. Other studies have shown that rural communities have a better understanding of CC, which can be attributed to the direct impact it has on their livelihoods [17][18][19]. Remarkably, the knowledge and perspectives of these communities regarding CC may sometimes differ from the scientific consensus.…”
Section: Introductionmentioning
confidence: 99%